Dental management of a child with EEC syndrome - (:unkn) unknown (My University, 1992)
Summary. The EEC syndrome is a condition characterized by ectrodactyly, ectodermal dysplasia and clefting of the lip and/or palate. Here we report a case of a boy with the EEC syndrome. The clinical and radiologic aspects of this condition, as well as the dental treatment, are reviewed. La dysplasie ectodermique, l'ectrodactyle et la fente palatine et labiale sont caractéristiques d'un syndrôme. L'aspect clinique, radiologique et le traitement dentaire d'un patient atteint de ce syndrôme, sont étudiés dans cet article. Das EEC Syndrom ist charakterisiert durch Ektrodaktylie, ektodermale Dysplasie und durch Lippenoder und Gaumenspalten. In diesem Bericht wird ein Fall mit EEC Syndrom beschrieben, die klinischen und röntgoloischen Aspekte dieses Syndromes, ebenso die zahnärztliche Behandlung dieses Falles. El sindrome EEC (EDF) es una condición caracterizada por ectrodactilidad, displasia ectodérmica y fisura (hendidura) del labio y/o paladar. Se reporta un caso con el síndrome EEC y los aspectos clínicos y radiográficos de la condición así como el tratmiento odontológico realizado. 1992 BSPD, IAPD and Blackwell Publishing Ltd